Competing cleavages in sub-Saharan Africa? How economic distance affects ethnic bloc politics - Jeffrey Conroy-Krutz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Does economic standing cross-cut ethnicity in African electoral politics? In many countries in the region, ethnicity appears to be a major consideration in individuals' political decision-making. However, there is significant variation in the extent to which coethnics support parties en bloc; while some ethnic groups exhibit high rates of similarity in terms of members' preferred parties, others are more fractionalized. One factor that might affect the probability that an individual will support the plurality-choice party of his or her ethnic group is relative economic standing. I expect that, as the distance between an individual's level of wealth and his or her ethnic group's median level of wealth increases, the probability of the member supporting the most-favoured party of their coethnics decreases. In other words, economic considerations can cross-cut ascriptive identities. I test this expectation with data from 27 countries included in the fifth round of the Afrobarometer and find that individuals who are significantly different, in terms of wealth, from other members of their ethnic group are significantly less likely to support their group's plurality-choice party. Specifically, economic difference increases non-partisanship and support for out-parties (i.e., those not their group's plurality choice). Further, being a member of a group that has greater levels of within-group inequality reduces support for a plurality-choice party, while living in a country with higher levels of between-group inequality increases support for a plurality-choice party. The results suggest that some ethnic groups' propensity towards bloc voting can be explained, at least partially, by group-level similarities in economic interests.
Keywords: 330; Africa; elections; ethnicity; inequality; parties